SIMULASI ISLAMIC FORWARD AGREEMENT PADA PEMBIAYAAN VALAS BANK SYARIAH DI INDONESIA - WUSHI ADILLA ARSYI (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2016)
The fluctuating exchange is so risky and can cause the loss to Islamic Banks. The hedging instrument on the exchange rate based on Islamic principles to manage this risk is needed. Dewan Syariah Nasional Majelis Ulama Indonesia (DSN MUI) has issued a fatwa related to it in fatwa No. 96/DSN-MUI/IV/2015 about Islamic Hedging Transactions (al-Tahawwuth al-Islam) on exchange. Given this fatwa, hedging simulation with forward agreement scheme may be applied in USD financing product in Islamic Bank. The research method used is simulation and comparison method between the outstanding of forex financing and premium and tenor of forward references. The result of this study shows that Islamic banks will benefit if doing islamic forward agreement. The reference premium and tenor recommended for calculating this Islamic forward agreement transactions based on the results of the research is the rate of return of FASBIS with a tenor of 6 months, with a gain of 3,461 trillion rupiah. This amount represents the highest potential nominal gain compared to other simulation results. Nevertheless, the use of FASBIS rewards are not always recommended and is only used temporarily in certain moments. However, when compared to conventional-based reference premiums, premium benchmark rate of FASBIS return may be an option for islamic banks and businesses to calculate the rate forward of Islamic forward agreement transactions.